PENERAPAN PEMBELAJARAN INTERAKTIF MELALUI METODE BERNYANYI DALAM MENGEMBANGKAN ASPEK SOSIAL EMOSIONAL ANAK - Cahya Yulianti; Catur Louisa; Fitri Nur’Aeni; Wanda Anggih Sabila; Lizza Suzanti (Fakultas Tarbiyah IIQ Jakarta, 2024)
The social-emotional aspect is understood as a crisis in child development that needs attention because it is related to the ability to interact and adjust according to the expectations of the surrounding environment. Appropriate learning methods and stimulation will make children's social-emotional development aspects develop optimally. This research aims to find effective learning methods for stimulating social-emotional aspects that are in accordance with children's character. The research used a qualitative-descriptive method with observation and interview techniques. The research subjects were 10 students in class B1 and 1 homeroom teacher at TK Islam Tirtayasa. The results showed that the social-emotional development of 6 out of 10 students was not optimal, especially in terms of a sense of responsibility for oneself. This can be seen where children have not been able to obey class rules, have not been able to restrain themselves, and have not been able to take responsibility for their behavior. Therefore, researchers use interactive learning through the singing method so that students can more easily understand the rules conveyed without feeling forced.